Optimization of a compact falling-droplet absorber for cooling power generation - Cola, Fabrizio (2018)
Refrigeration has become a necessary component for comfort living. Absorption refrigeration is a valid option for waste-heat-to cool conversion. Coupling this technology with cheap heat energy sources is an interesting prospect, however downsizing of this type or chiller for small environments has been proven difficult, especially regarding the absorber. Large interface area between the two operating fluids returns higher absorption rates, but lack of control on the fluid distribution results in an inefficient use of the space available. This study proposes a space-efficient design based on finned-plate technology coupled with a droplet flow regime. Manufacturing through 3D printing technique is used to study the effect of fins shape. Droplet behaviour is firstly studied with an analytical model based on the variational approach. Experimental results were obtained using a high speed camera employed to validate the analytical results and obtain qualitative and quantitative data to complete the analysis. The results show that the analytical model reproduces with sufficient accuracy the droplet dynamics in some regions. The rhomboidal geometry with 120° angle proved able to produce the smallest droplets without allowing merging of more droplets, ensuring the maintenance of droplet flow. Disturbances in the droplet profiles were observed, caused by the pin-droplet interaction. Further study is required to refine the model (to account for these disturbances) and obtain a more precise prediction of the droplet sizes.